SARS-CoV-2 antibodies in dogs and cats in a highly infected area of Brazil during the pandemic - Jarrah, Samar Afif; Kmetiuk, Louise Bach; Valleriani, Fabrizia; Bonfini, Barbara; Lorusso, Alessio; Vasinioti, Violetta; Decaro, Nicola; dos Santos, Marco Tulio; Spohr, Kledir Anderson Hofstaetter; Pratelli, Annamaria; Serroni, Anna; Capista, Sara; et al. (Frontiers in Veterinary Science, 2023)
the state of Mato Grosso had the second highest mortality rate in Brazil, with 427.4 deaths/100,000 inhabitants. However, no large-scale study among dogs and cats in such highly infected areas of Brazil has so far been conducted. Accordingly, the present study reports on a serosurvey among dogs and cats in Cuiabá, capital of Mato Grosso from November 2020 to July 2021, where the human mortality rate was 605/100,000 at that time. Overall, 33/762 dogs (4.3%) and 4/182 cats (2.2%) were found to be seropositive for SARS-CoV-2 through ELISA, and 3/762 dogs (0.4%) and 3/182 cats (1.6%) were seropositive through the serum neutralization test. Cats presented higher seroprevalence with higher titers of neutralizing antibodies. Although N-protein based ELISA may be a good screening test, cross-reactivity with other canine coronaviruses may impair its diagnostic use among dogs.